HUBUNGAN DUKUNGAN KELUARGA TERHADAP KEPATUHAN DIET HIPERTENSI PADA LANSIA DI KELURAHAN KALIBEBER - Fatata Mahira; Fifi Alviana; Anisa Ell Raharyani (Fakultas Ilmu Kesehatan (FIKES) Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2024)
Background: Hypertension is classified as a silent killer disease where the patient does not know that he has hypertension before checking and examining him. Hypertension, if now no longer handled properly, can purpose complications. Hypertension sufferers need family support in implementing a diet. Objective: to determine the relationship between family support and hypertension diet compliance in the elderly in Kalibeber Village. Method: researches was using quantitative research with analytical descriptive methods with a cross- sectional approach using questionnaires. The sampling technique used consecutive sampling with a population of 93 respondents. The information evaluation method used of the Spearman rank test. Results: There were a relationship between family support and hypertension diet compliance in the elderly in Kalibeber Village with a p value of 0.000 <0.05 with a correlation coefficient of 0.657 which means strong. Conclusion: There were a relationship between family support and hypertension diet compliance in the elderly in Kalibeber Village.